Ultra-thin heat spreader super-hydrophilic micro-nano structure liquid wick and preparation method thereof
By using ultra-fast laser on ultra-thin heat-smooth plates to prepare liquid absorbing cores with micro-arrays and nanosome structures, the problem of degradation of capillary performance of ultra-thin heat pipes is solved, high capillary force and permeability are achieved, and heat transfer efficiency is improved and cooling capacity.
Patent Information
- Application Number
- CN202010760183.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-07-31
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2040-07-31
AI Technical Summary
The existing liquid absorbent cores are difficult to meet the high capillary force and high permeability requirements of ultra-thin heat pipes. Especially when the thickness of the heat pipe is reduced to below 0.4mm, the capillary performance is significantly reduced, the water and gas resistance are improved, and the heat transfer efficiency is reduced.
Ultrafast laser is used to prepare ultra-hyalurophilic micro-nanostructured liquid absorbing core of ultra-thin heat-smooth plate. By forming periodically distributed micro-arrays and surrounding channels on the cover plate of the heat-smooth plate, the surface is densely distributed to form a rich nano-sized substructure. Micro-nano-full-covered structure and a high-surface energy oxide coating is provided on the surface to improve capillary force and permeability.
It significantly improves the liquid absorption capacity and evaporation capacity of the liquid absorption core, reduces water and gas resistance, ensures the oriented heat dissipation capacity, avoids the collapse of the cover plate of the heat-smoothing plate, and achieves stable work of 0.2-0.4mm ultra-thin heat pipe , and improves heat dissipation efficiency.
Smart Images

Figure CN111735331B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a liquid wick for various ultra-thin heat pipes and vapor chambers, in particular to a high-performance liquid wick based on a super-hydrophilic micro-nano structure, and belongs to the technical field of heat pipes. Background Art
[0002] With the rapid development of microelectronics technology and the electronic information industry, various electronic devices and components, especially ultra-thin mobile devices represented by smart phones and tablets, are constantly developing in the direction of high performance, integration, miniaturization and lightness. Higher chip heat flux density, smaller heat dissipation space and more difficult heat dissipation conditions have put forward higher requirements on the heat dissipation capacity and further miniaturization of the heat dissipation device. The heat dissipation problem of high heat flux density has become one of the key limiting factors restricting the further development of electronic equipment.
[0003] As a high-efficiency two-phase heat transfer device based on boiling phase change heat transfer, the heat spreader (VC) and the heat pipe (for convenience, the heat spreader described below includes a heat pipe, and the heat spreader described in this patent also includes a heat pipe) are widely used in electronic devices such as smart phones and laptops due to their excellent thermal conductivity, good isothermal properties and reliability. With the increasing thinness of electronic devices, ultra-thin heat pipes have also become an effective means and preferred solution for heat dissipation in a small space. Ultra-thin heat pipes are generally composed of a tube body, a sealing head, a wick and a working medium, and their main structure includes an evaporation section, an insulation section, a condensation section and a sealed shell. In the evaporation section, liquid water absorbs the heat generated by the chip and evaporates into steam. It is transported through the vapor phase of the steam channel in the insulation section to the condensation section, and the steam is reduced to liquid water through the heat release of the condensation section, and then refluxes to the evaporation section for continuous back and forth circulation to quickly dissipate the heat of the chip. The heat transfer performance, heat transfer efficiency and heat transfer limit of the heat pipe mainly depend on the capillary pressure provided by the wick and the penetration reflux rate of the liquid in the wick. Traditional wicks mainly include wire mesh wicks, powder / fiber sintered wicks, groove wicks and composite wicks. The thickness of the wicks required for ultra-thin heat pipes is also constantly decreasing, resulting in an increase in the interface shear force caused by the internal gas-liquid high-speed convection and a decrease in the heat transfer capacity. There are currently two main development directions: one is to optimize the traditional wick to meet the requirements of ultra-thin heat pipes, such as using a sintered copper mesh core prepared by chemical deposition and sintering, or a composite wick structure that integrates wire mesh, grooves and powder sintering. This type of method increases the complexity and cost of the ultra-thin heat pipe manufacturing process and is difficult to further reduce the thickness. The second method is to use etching methods such as reactive ion etching, electrospark machining, electrolytic machining, surface coating, etc. to prepare a wick structure on the inner wall of an ultra-thin heat pipe. These methods are relatively complex, expensive, and not environmentally friendly. Laser processing is flexible and non-contact, and can produce complex capillary structures with a certain degree of roughness. It is a promising method for preparing wicks and has been relatively active in recent years. For example, nanosecond lasers are used to carve out crisscrossing tiny grooves on the wall of heat pipes, and nanosecond lasers are used to scan the groove surface of aluminum substrates alternately to produce continuous capillary super-hydrophobic and super-hydrophilic structures with fuzzy morphology. Lasers are used to process pin-wing and groove structures on copper plates, and nanosecond lasers are used to prepare slope groove capillary structures, micro-groove structures of unequal width, and high, deep and wide composite groove structures.
[0004] The wicks prepared by the above methods can be used for heat pipes of general thickness. When the thickness of the heat pipe is less than 0.4 mm, its capillary performance will be significantly reduced, the water resistance and gas resistance will be significantly increased, and the heat transfer efficiency will drop rapidly. General wicks are difficult to meet the needs.
[0005] Therefore, how to provide an ultra-thin heat spreader with an ultra-hydrophilic micro-nano structure liquid-absorbing core with better performance and a preparation method thereof is one of the technical problems that urgently need to be solved in the art. Summary of the invention
[0006] In view of this, the present invention provides an ultra-thin heat spreader with a super-hydrophilic micro-nano structure liquid absorbent core and a preparation method thereof, so as to solve the problem of preparing a liquid absorbent core with high capillary force and high permeability of an ultra-thin heat spreader. Although existing patents also involve nanosecond laser processing, groove structure and super-hydrophilic treatment, none of them involve a micro-nano structure for achieving super-hydrophilicity, nor do they provide capillary force and permeability data of the liquid absorbent core.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] An ultra-thin vapor chamber super-hydrophilic micro-nano structure liquid wick, comprising a liquid wick and a vapor chamber cover, wherein the liquid wick is directly prepared on the vapor chamber cover;
[0009] The liquid wick is composed of a periodically distributed micron array and channels around it; the surface of the micron array and the surface of the channels around it are densely distributed with nano-scale substructures, and the three constitute a micro-nano full-coverage structure containing rich micro-cavities; the surface of the micro-nano full-coverage structure is provided with a high surface energy oxide coating.
[0010] Preferably, the micron array is an array composed of a plurality of micron cones; the spacing between each micron cone is 1-300 microns; the diameter of each micron cone is 1-200 microns; the slope of each micron cone is 5-45°; the height of each micron cone is 10-70% of the thickness of the vapor chamber cover plate;
[0011] Or, the micron array is an array composed of multiple micron rectangular blocks; and the spacing between each micron rectangular block is 10-500 microns; the aspect ratio of each micron rectangular block is 1:1-1:10; the slope of each micron rectangular block is 5-45°; the height of each micron rectangular block is 10-70% of the thickness of the heat spreader cover.
[0012] Preferably, the scale of the nanoscale substructure is 1-1000 nanometers; and the nanoscale substructure is corrugated or granular.
[0013] Preferably, the thickness of the oxide coating is less than 5 nanometers; and the material of the oxide coating is SiO2 and / or TiO2.
[0014] Preferably, the wick may be in the shape of one or a combination of square, rectangle, cross, triangle, strip, circle and radial.
[0015] Preferably, the material of the heat spreader cover is one or more of copper, copper alloy, aluminum, aluminum alloy and stainless steel.
[0016] The present invention also provides a method for preparing an ultra-thin vapor chamber super-hydrophilic micro-nanostructure liquid wick, comprising the following steps:
[0017] 1) The heat spreader cover plate is subjected to pre-processing such as cutting and cleaning. The thickness of the heat spreader cover plate may be 0.2 to 1 mm, and the typical thickness may be 0.2 to 0.4 mm;
[0018] 2) According to the shape requirements of the heat spreader cover for the wick area, the ultrafast laser scanning area is compiled into various shapes such as square, rectangle, cross, T-shape, L-shape, I-shape, triangle, strip, circle, radial shape and combinations thereof, and the preparation work is performed in the above-mentioned shape areas;
[0019] 3) focusing an ultrafast laser onto the surface of the wick, optimizing the process parameters of the ultrafast laser, including average power, single pulse energy, repetition frequency, focal spot size, scanning speed, action time, number of scans and scanning path, so that the beam energy flux density in the laser action area is higher than the ablation threshold of the heat spreader cover material, and vaporizing and evaporating the material based on the ablation mechanism to form an array of the periodically distributed multiple micron cones / multiple micron rectangular blocks and the surrounding channels, and forming nano-corrugated / nano-granular nano-substructures on the surfaces of the multiple micron cones / multiple micron rectangular blocks and the surrounding channels based on the ablation and induction mechanism of the ultrafast laser;
[0020] 4) performing high surface energy treatment on the surface of the micro-nano substructure to form a super-hydrophilic micro-nano structure liquid-absorbing core;
[0021] 5) The prepared super-hydrophilic micro-nano structure liquid absorbent core is sequentially subjected to ultrasonic cleaning, purging, and drying, and then vacuum packaging to obtain the super-hydrophilic micro-nano structure liquid absorbent core product.
[0022] Preferably, the high surface energy treatment in step 4) is immersion, spraying, evaporation, sputtering of SiO2 / TiO2 to form an oxide coating to achieve super-hydrophilic properties with strong capillary force and permeability; and the thickness of the oxide coating is less than 5 nanometers.
[0023] Preferably, the wavelength of the ultrafast laser may be near-infrared light, green light or ultraviolet light; the repetition frequency of the ultrafast laser is 10KHz-10000KHz, the average power is 1-500W, the scanning speed is 10-10000mm / s, the focal spot size is 1-300 microns, and the number of scans is single or multiple.
[0024] Preferably, the ultrafast laser is a picosecond laser or a femtosecond laser, the pulse width of the picosecond laser is 1-1000 picoseconds, and the pulse of the femtosecond laser is 50-1000 femtoseconds.
[0025] Compared with the prior art, the present invention has achieved the following technical effects:
[0026] (1) The present invention focuses on ultra-thin heat pipes of 0.2-0.4 mm. As is known to all, when the thickness of the heat pipe is reduced to below 0.4, the capillary performance of the wick will be significantly reduced, the water resistance and gas resistance will be significantly increased, and the heat transfer efficiency will decrease rapidly. The super-hydrophilic micro-nanostructure wick prepared by the present invention, whether it is the surface of the periodically distributed micron cone array and micron rectangular array, or the surface of the surrounding channels, are densely distributed with nano-scale ripples or particle substructures. The array, channel and surface contain micro-nanostructures rich in micro-cavities to form a strong capillary force, which significantly improves the wick's ability to absorb liquid;
[0027] (2) The micron-scale cone array and rectangular array, together with the rich nano-substructures on their surfaces and the nano-structures on the channel surfaces, together constitute excellent superhydrophilic properties. In the evaporation section, the high-temperature bubble nucleation evaporation heat dissipation mechanism based on the superhydrophilic surface will significantly improve the evaporation capacity. Studies have shown that when evaporating at a high temperature exceeding 100 degrees, the superhydrophilic surface will continuously generate a large number of bubbles that quickly detach from the surface, thereby improving the dissipation of heat. Other surfaces will form a water film to cover the high-temperature surface, hindering the dissipation of heat flow. At the same temperature, the heat dissipation heat flux of the superhydrophilic surface is dozens of times higher than that of the hydrophobic surface or the superhydrophobic surface;
[0028] (3) The periodically distributed micron cone array and micron rectangular array are surrounded by well-connected channels, which help the wick to balance the directional wicking capacity, ensure the heat dissipation capacity in all directions, and avoid the insufficient directional wicking of a simple groove-shaped wick.
[0029] (4) The interconnected channels between micron cones and micron rectangles form unobstructed liquid and vapor channels, which helps reduce water resistance and gas resistance and improve overall performance;
[0030] (5) The periodically distributed micron cone array and micron rectangular array provide strong support for the liquid channel and the gas channel, avoiding the collapse of the heat spreader cover under pressure, and ensuring the long-term stable operation of the liquid wick and the heat spreader;
[0031] (6) The wick is directly prepared on the vapor chamber cover plate without increasing the thickness, which is conducive to realizing an ultra-thin vapor chamber of 0.2-0.4 mm;
[0032] (7) The periodically distributed micron cone array and micron rectangular array in the liquid wick of the present invention, as well as the interconnected liquid channels and the rich micro-cavity substructures on the surface, are prepared by high-power picosecond laser or femtosecond laser, and the cone, rectangular and channel micro-structures are formed by laser ablation mechanism, and a variety of nano-structures are formed by ablation induction mechanism under optimized process, which is a multifunctional preparation method; at the same time, the laser beam can be programmed by computer to control the scanning galvanometer, and prepare liquid wick patterns of almost any shape in one step, such as square, rectangular, T-shaped, L-shaped, I-shaped, triangle, strip, circular, radial and other shapes and their combinations, to meet the heat dissipation requirements of various heat spreaders, which is a flexible and efficient preparation method. In addition, by controlling the process parameters such as the energy flux density and scanning speed of the ultrafast laser beam, the depth of the micro-nano structure, that is, the depth of the liquid channel and the steam channel can be accurately controlled, so that the steam cavity structure and liquid cavity structure and volume distribution inside the heat pipe can be regulated and optimized to ensure its good capillary water absorption performance and low water resistance and thermal resistance. The laser preparation process is stable, highly repeatable, and has a high yield rate. It is a practical and reliable preparation method. By increasing the laser power and taking a variety of measures to increase the processing speed, the laser one-step preparation of the micro-nanostructure of the absorbent core can be an efficient and cost-controlled preparation method. Compared with the traditional preparation methods of the existing wick powder spray sintering and copper wire mesh wick, the laser method for preparing the wick has fewer process steps, shorter processes, higher efficiency, better structural consistency, higher stability, and better overall performance, and can achieve the lowest heat pipe thickness and the best heat dissipation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic diagram of a periodically distributed micron cone array and nano substructure and surrounding channels of an ultra-thin vapor chamber super-hydrophilic micro-nano structure liquid absorbent core of the present invention;
[0034] Figure 2 A schematic diagram of a periodically distributed micron rectangular array and nano substructure and surrounding channels of an ultra-thin vapor chamber super-hydrophilic micro-nano structure liquid absorbent core of the present invention;
[0035] Figure 3 The actual photograph of the copper alloy L-shaped super-hydrophilic micro-nano structure liquid wick of the ultra-thin heat spreader and the water drop contact angle measurement result of the present invention;
[0036] Figure 4 The actual photograph of the aluminum alloy T-shaped super-hydrophilic micro-nano structure liquid wick of the ultra-thin heat spreader and the water drop contact angle measurement result;
[0037] Figure 5 The actual photograph of the stainless steel I-shaped super-hydrophilic micro-nano structure liquid absorbent core of the ultra-thin heat spreader and the water drop contact angle processing result;
[0038] In the figure: 1, liquid-absorbing core; 11, channel; 12, nanoscale substructure; 13, micron cone; 14, micron rectangle. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] An ultra-thin heat spreader with super-hydrophilic micro-nanostructure liquid-absorbing core, comprising a liquid-absorbing core 1 and a heat spreader cover, wherein the liquid-absorbing core is directly prepared on the heat spreader cover; the liquid-absorbing core 1 is composed of a periodically distributed micrometer array and channels 11 around it; the surface of the micrometer array and the surface of the channels 11 around it are densely distributed with nanometer-scale substructures 12, and the three constitute a micro-nano full-coverage structure; the surface of the micro-nano full-coverage structure is provided with an oxide coating. The scale of the nanometer-scale substructure 12 is 1-1000 nanometers; and the nanometer-scale substructure 12 is corrugated or granular. The thickness of the oxide coating is less than 5 nanometers; and the material of the oxide coating is SiO 2 and / or TiO 2 .
[0041] The micron array is an array composed of a plurality of micron cones 13; the spacing between each micron cone 13 is 1-300 microns; the diameter of each micron cone 13 is 1-200 microns; the slope of each micron cone 13 is 5-45°; the height of each micron cone 13 is 10-70% of the thickness of the vapor chamber cover plate;
[0042] Alternatively, the micron array is an array composed of a plurality of micron rectangular blocks 14; and the spacing between each of the micron rectangular blocks 14 is 10-500 microns; the aspect ratio of each of the micron rectangular blocks 14 is 1:1-1:10; the slope of each of the micron rectangular blocks 14 is 5-45°; and the height of each of the micron rectangular blocks 14 is 10-70% of the thickness of the heat spreader cover.
[0043] Example 1
[0044] The preparation method of the ultra-thin copper alloy vapor chamber super-hydrophilic micro-nano structure liquid wick comprises the following steps:
[0045] (1) The upper plate or the lower plate of the copper alloy soaking plate is subjected to pre-treatment such as cutting and cleaning. The thickness of the copper alloy cover plate can be 0.2 to 1 mm, and 0.4 mm is selected;
[0046] (2) The wick is directly prepared on the copper alloy vapor chamber cover. According to the shape requirements of the vapor chamber for the wick area, the scanning area of the ultrafast laser is prepared into various shapes such as square, rectangle, cross, T-shape, L-shape, I-shape, triangle, strip, circle, radial shape and their combination. In this embodiment, the L shape is selected to prepare the micro-nano structure in the above-mentioned shape area;
[0047] (3) Picosecond laser is used, the wavelength is near-infrared light, the pulse width of the picosecond laser is 1-1000 picoseconds, the repetition frequency can be 10KHz-10000KHz, the average power can be 1-500W, the scanning speed can be 10-10000mm / s, the focal spot size is 1-300 microns, and the number of scans is single. Focus the picosecond laser on the surface of the copper alloy heat spreader cover plate, optimize the eight process parameters of the picosecond laser, including the average power, single pulse energy, repetition frequency, focal spot size, scanning speed, action time, number of scans, and scanning path, so that the beam energy flux density in the laser action area is higher than the ablation threshold of the heat spreader metal material, and the vaporization and evaporation of the material generated based on the ablation mechanism forms the periodic distribution and the micron cone array or micron rectangular array and the surrounding channels, and at the same time, based on the ablation and induction mechanism of the picosecond laser, a nano-corrugated substructure is formed on the surface of the micron cone and the micron rectangular surface and the surrounding channel surface; Based on the above process, the picosecond laser prepares a periodically distributed micron cone array, with a cone spacing of 1-300 microns, a cone diameter of 1-200 microns, a cone slope of 5-45°, and a cone height of 10-70% of the plate thickness; the space around the micron cone constitutes a channel; the surface of the micron cone and the surrounding channel surface are densely distributed with nanoparticles, the scale of which is 1-1000 nanometers;
[0048] (4) Spraying SiO on the surface of the micro-nano structure 2 , the coating thickness is controlled below 5 nanometers, forming a super-hydrophilic micro-nano liquid-absorbing core structure;
[0049] (5) The prepared super-hydrophilic micro-nano structure liquid absorbent core is sequentially subjected to ultrasonic cleaning, purging, and drying, and then vacuum packaging to obtain the super-hydrophilic micro-nano structure copper alloy liquid absorbent core product.
[0050] The ultra-thin copper alloy heat spreader super hydrophilic micro-nano structure liquid wick has the following features: a micron cone array is periodically distributed on the surface of the copper alloy heat spreader cover, and nanoparticle substructures are densely distributed on the surface of each micron cone and the surface of the surrounding channels to form a micro-nano full coverage structure. The micro-nano structure is not treated or sprayed with SiO 2 After treatment, a super-hydrophilic micro-nano absorbent core is formed, which has strong capillary force and permeability. Its capillary force is greater than 1500Pa and its permeability is greater than 5*10 -11 m 2The liquid wick with super-hydrophilic micro-nanostructure features can be in various shapes such as square, rectangle, cross, T-shaped, L-shaped, I-shaped, triangle, strip, circle, radial and combinations thereof to meet various heat dissipation requirements of heat spreaders. The present embodiment is in L shape.
[0051] Example 2
[0052] The preparation method of the ultra-thin aluminum alloy vapor chamber super-hydrophilic micro-nano structure liquid wick comprises the following steps:
[0053] (1) The aluminum alloy soaking plate cover is subjected to pre-treatment such as cutting and cleaning. The thickness of the aluminum alloy cover can be 0.2 to 1 mm, and 0.3 mm is selected;
[0054] (2) The wick is directly prepared on the vapor chamber cover. According to the shape requirements of the vapor chamber for the wick area, the scanning area of the ultrafast laser is prepared into various shapes such as square, rectangle, cross, T-shape, L-shape, I-shape, triangle, strip, circle, radial shape and combinations thereof. In this embodiment, T-shape is selected to prepare micro-nano structures in the above-mentioned shape areas;
[0055] (3) A femtosecond laser is used, the wavelength is green light, the pulse width of the femtosecond laser is 10-1000 femtoseconds, the repetition frequency can be 10KHz-10000KHz, the average power can be 1-500W, the scanning speed can be 10-10000mm / s, the focal spot size is 1-300 microns, and the number of scans is single. Focus the femtosecond laser on the surface of the copper alloy cover plate, optimize eight process parameters of the femtosecond laser, including average power, single pulse energy, repetition frequency, focal spot size, scanning speed, action time, number of scans, and scanning path, so that the beam energy flux density in the laser action area is higher than the ablation threshold of the metal material of the heat spreader, and the vaporization and evaporation of the material generated based on the ablation mechanism forms the periodically distributed and sized micron cone array or micron rectangular array and surrounding channels, and at the same time, based on the ablation and induction mechanism of the femtosecond laser, a nano-wave corrugation substructure is formed on the surface of the micron cone and micron rectangular and the surrounding channel surface; Based on the above process, the femtosecond laser prepares a periodically distributed micron rectangular array, the rectangular spacing is 10-500 microns, the aspect ratio is 1:1-1:10, the surrounding slope is 5-45°, and the rectangular height is 10-70% of the plate thickness; the space around the micron rectangular constitutes a channel; the nano-scale substructure densely distributed on the surface of the micron rectangular and the surrounding channel surface is a nano-wave, and its scale is 1-1000 nanometers;
[0056] (4) Spraying TiO on the surface of the micro-nano structure 2 , the coating thickness is controlled below 5 nanometers, forming a super-hydrophilic micro-nano liquid-absorbing core structure;
[0057] (5) The prepared super-hydrophilic micro-nano structure liquid absorbent core is sequentially subjected to ultrasonic cleaning, purging, and drying, and then vacuum packaging to obtain the super-hydrophilic micro-nano structure copper alloy liquid absorbent core product.
[0058] The ultra-thin aluminum alloy heat spreader super hydrophilic micro-nano structure liquid wick has the following features: a micron rectangular array is periodically distributed on the surface of the copper alloy of the heat spreader, and nano-corrugated sub-structures are densely distributed on the surface of each micron rectangular block and the surface of the surrounding channels to form a micro-nano full coverage structure. The micro-nano structure is not treated or sprayed with SiO 2 After treatment, a super-hydrophilic micro-nano absorbent core is formed, which has strong capillary force and permeability. Its capillary force is greater than 1300Pa and its permeability is greater than 4*10 - 11 m 2 The liquid wick with super-hydrophilic micro-nanostructure features can be in various shapes such as square, rectangle, cross, T-shaped, L-shaped, I-shaped, triangle, strip, circle, radial and combinations thereof to meet various heat dissipation requirements of heat spreaders. The present embodiment is T-shaped.
[0059] Example 3
[0060] The preparation method of the stainless steel vapor chamber super-hydrophilic micro-nanostructure liquid wick comprises the following steps:
[0061] (1) The upper plate or the lower plate of the stainless steel soaking plate is subjected to pre-treatment such as cutting and cleaning. The thickness of the stainless steel cover plate can be 0.2 to 1 mm, and 0.2 mm is selected;
[0062] (2) The wick is directly prepared on the vapor chamber cover. According to the shape requirements of the vapor chamber for the wick area, the scanning area of the ultrafast laser is prepared into various shapes such as square, rectangle, cross, T-shape, L-shape, I-shape, triangle, strip, circle, radial shape and combinations thereof. In this embodiment, the I-shape is selected, and the micro-nano structure is prepared in the above-mentioned shape area;
[0063] (3) Picosecond laser is used, the wavelength is near infrared, the pulse width of the picosecond laser is 1-1000 picoseconds, the repetition frequency can be 10KHz-10000KHz, the average power can be 1-500W, the scanning speed can be 10-10000mm / s, the focal spot size is 1-300 microns, and the number of scans is single. Focus the picosecond laser on the surface of the copper alloy cover plate, optimize the eight process parameters of the picosecond laser, including the average power, single pulse energy, repetition frequency, focal spot size, scanning speed, action time, number of scans, and scanning path, so that the beam energy flux density in the laser action area is higher than the ablation threshold of the metal material of the heat spreader, and the vaporization and evaporation of the material generated based on the ablation mechanism forms the periodically distributed and sized micron cone array or micron rectangular array and the surrounding channels, and at the same time, based on the ablation and induction mechanism of the picosecond laser, a nano-corrugated substructure is formed on the surface of the micron cone and the micron rectangular block and the surrounding channel surface; Based on the above process, the picosecond laser prepares a periodically distributed micron cone array, the cone spacing is 1-300 microns, the cone diameter is 1-200 microns, the cone slope is 5-45°, and the cone height is 10-70% of the plate thickness; the space around the micron cone constitutes a channel; the surface of the micron cone and the surrounding channel surface are densely distributed with nanoparticles, the scale of which is 1-1000 nanometers;
[0064] (4) Spraying SiO on the surface of the micro-nano structure 2 , the coating thickness is controlled below 5 nanometers, forming a super-hydrophilic micro-nano liquid-absorbing core structure;
[0065] (5) The prepared super-hydrophilic micro-nano structure liquid absorbent core is sequentially subjected to ultrasonic cleaning, purging, and drying, and then vacuum packaging to obtain the super-hydrophilic micro-nano structure copper alloy liquid absorbent core product.
[0066] The ultra-thin stainless steel heat spreader super-hydrophilic micro-nano structure liquid absorbent core has the following characteristics: micro-cone arrays are periodically distributed on the stainless steel surface, and nano-particle substructures are densely distributed on the surface of each micro-cone and the surrounding channel surface to form a micro-nano full coverage structure. The micro-nano structure is not treated or sprayed with SiO2 to form a super-hydrophilic micro-nano liquid absorbent core, which has a strong capillary force and permeability. The capillary force is greater than 1400Pa and the permeability is greater than 4.5*10 -11 m 2 The liquid wick with super-hydrophilic micro-nanostructure features can be in various shapes such as square, rectangle, cross, T-shaped, L-shaped, I-shaped, triangle, strip, circle, radial and combinations thereof to meet various heat dissipation requirements of heat spreaders. The present embodiment is in an I-shaped shape.
[0067] In some other embodiments, the wick may be in the shape of one or more combinations of square, rectangle, cross, triangle, strip, circle and radial.
[0068] In some other embodiments, the material of the heat spreader cover is one or more of copper, copper alloy, aluminum, aluminum alloy and stainless steel.
[0069] Compared with the prior art, the present invention has achieved the following technical effects:
[0070] (8) The present invention focuses on ultra-thin heat pipes of 0.2-0.4 mm. As is known to all, when the thickness of the heat pipe is reduced to below 0.4, the capillary performance of the wick will be significantly reduced, the water resistance and gas resistance will be significantly increased, and the heat transfer efficiency will drop rapidly. The super-hydrophilic micro-nanostructure wick prepared by the present invention, whether it is the surface of the periodically distributed micron cone array and micron rectangular array, or the surface of the surrounding channels, are densely distributed with nano-scale ripples or particle substructures. The array, channel and surface rich micro-nanostructures have formed a strong capillary force, which significantly improves the wick's ability to absorb liquid;
[0071] (9) The micron-scale cone array and rectangular array, together with the rich nano-substructures on their surfaces and the nano-structures on the channel surfaces, together constitute excellent superhydrophilic properties. In the evaporation section, the high-temperature bubble nucleation evaporation heat dissipation mechanism based on the superhydrophilic surface will significantly improve the evaporation capacity. Studies have shown that when evaporating at a high temperature exceeding 100 degrees, the superhydrophilic surface will continuously generate a large number of bubbles that quickly detach from the surface, thereby improving the dissipation of heat. Other surfaces will form a water film to cover the high-temperature surface, hindering the dissipation of heat flow. At the same temperature, the heat dissipation heat flux of the superhydrophilic surface is dozens of times higher than that of the hydrophobic surface or the superhydrophobic surface;
[0072] (10) The periodically distributed micron cone array and micron rectangular array are surrounded by well-connected channels, which help the wick to balance the directional wicking capacity, ensure the heat dissipation capacity in all directions, and avoid the insufficient directional wicking of a simple groove-shaped wick.
[0073] (11) The interconnected channels between micron cones and micron rectangles form unobstructed liquid and vapor channels, which helps reduce water resistance and gas resistance and improve overall performance;
[0074] (12) The periodically distributed micron cone array and micron rectangular array provide strong support for the liquid channel and the gas channel, avoiding the collapse of the heat spreader cover under pressure, and ensuring the long-term stable operation of the liquid wick and the heat spreader;
[0075] (13) The wick is directly prepared on the heat spreader cover without increasing the thickness, which is conducive to realizing an ultra-thin heat spreader of 0.2-0.4 mm;
[0076] The periodically distributed micron cone array and micron rectangular array and the interconnected liquid channels in the liquid absorbent core of the present invention are prepared by high-power picosecond laser or femtosecond laser, and the cone, rectangular and channel micron structures are formed by laser ablation mechanism, and a variety of nanostructures are formed by ablation induction mechanism under optimized process, which is a multifunctional preparation method; at the same time, the laser beam can be programmed by computer to control the scanning galvanometer, and prepare liquid absorbent core patterns of almost any shape in one step, such as square, rectangular, T-shaped, L-shaped, I-shaped, triangle, strip, circular, radial and other shapes and their combinations, to meet the heat dissipation requirements of various heat spreaders, which is a flexible and efficient preparation method. In addition, by controlling the process parameters such as the energy flux density and scanning speed of the ultrafast laser beam, the depth of the micro-nano structure, that is, the depth of the liquid channel and the steam channel can be accurately controlled, so that the vapor cavity structure and liquid cavity structure and volume distribution inside the heat pipe can be regulated and optimized to ensure its good capillary water absorption performance and low water resistance and thermal resistance. The laser preparation process has stable process, high repeatability and high yield, and is a practical and reliable preparation method. By increasing the laser power and taking a variety of measures to increase the processing speed, the laser one-step preparation of the micro-nanostructure of the absorbent core can be an efficient and cost-controlled preparation method. Compared with the traditional preparation methods of the existing absorbent core powder spray sintering and copper wire mesh absorbent core, the laser method for preparing the absorbent core has fewer process steps, shorter process, higher efficiency, better structural consistency, higher stability, better comprehensive performance, and can achieve the lowest heat pipe thickness and the best heat dissipation effect.
[0077] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. An ultra-thin heat spreader with ultra-hydrophilic micro-nanostructure liquid wick, characterized in that: It comprises a liquid wick (1) and a heat spreader cover, wherein the liquid wick is directly prepared on the heat spreader cover; The liquid wick (1) is composed of a periodically distributed micron array and surrounding channels (11); the surface of the micron array and the surface of the surrounding channels (11) are densely distributed with nanoscale substructures (12), and the three constitute a micro-nano full-coverage structure containing abundant micro-cavities; the surface of the micro-nano full-coverage structure is provided with a high surface energy oxide coating; The micron array is an array composed of a plurality of micron cones (13); the spacing between each of the micron cones (13) is 1-300 microns; the diameter of each of the micron cones (13) is 1-200 microns; the slope of each of the micron cones (13) is 5-45°; the height of each of the micron cones (13) is 10-70% of the thickness of the heat spreader cover plate; Or, the micron array is an array composed of a plurality of micron rectangular blocks (14); the spacing between each micron rectangular block (14) is 10-500 microns; the aspect ratio of each micron rectangular block (14) is 1:1-1:10; the slope of each micron rectangular block (14) is 5-45°; the height of each micron rectangular block (14) is 10-70% of the thickness of the heat spreader cover; The scale of the nanoscale substructure (12) is 1-1000 nanometers; and the nanoscale substructure (12) is corrugated or granular.
2. The ultra-thin vapor chamber super-hydrophilic micro-nano structure liquid wick according to claim 1, characterized in that: The thickness of the oxide coating is less than 5 nanometers; and the material of the oxide coating is SiO2 or TiO2.
3. The ultra-thin vapor chamber super-hydrophilic micro-nano structure liquid wick according to claim 1, characterized in that: The liquid absorbent core (1) is in the shape of one or a combination of square, rectangle, cross, T-shape, L-shape, I-shape, triangle, strip, circle and radial shape.
4. The ultra-thin vapor chamber super-hydrophilic micro-nanostructure liquid wick according to claim 1, characterized in that: The material of the heat spreader cover is one or more of copper, copper alloy, aluminum, aluminum alloy and stainless steel.
5. The method for preparing an ultra-thin vapor chamber super-hydrophilic micro-nano structure liquid wick according to claim 1, characterized in that: The following steps are included: 1) The heat spreader cover plate is subjected to pre-processing such as cutting and cleaning. The thickness of the heat spreader cover plate may be 0.2 to 1 mm, and the typical thickness may be 0.2 to 0.4 mm; 2) According to the shape requirements of the heat spreader cover for the area of the wick (1), the ultrafast laser scanning area is compiled into various shapes such as square, rectangle, cross, T-shape, L-shape, I-shape, triangle, strip, circle, radial shape and combinations thereof, and the preparation work is performed in the above-mentioned shape areas; 3) focusing an ultrafast laser onto the surface of the liquid wick (1), optimizing the process parameters of the ultrafast laser, including average power, single pulse energy, repetition frequency, focal spot size, scanning speed, action time, number of scans and scanning path, so that the beam energy flux density in the laser action area is higher than the ablation threshold of the heat spreader cover material, and the vaporization and evaporation of the material generated based on the ablation mechanism forms an array of the periodically distributed multiple micron cones (13) / multiple micron rectangular blocks (14) and the surrounding channels (11), and at the same time, based on the ablation and induction mechanism of the ultrafast laser, nano-corrugated / nano-granular nanoscale substructures (12) are formed on the surfaces of the multiple micron cones (13) / multiple micron rectangular blocks (14) and the surrounding channels (11); 4) performing high surface energy treatment on the surface of the nanoscale substructure (12) to form a super-hydrophilic micro-nanostructure liquid-absorbing core; 5) The prepared super-hydrophilic micro-nano structure liquid absorbent core is sequentially subjected to ultrasonic cleaning, purging, and drying, and then vacuum packaging to obtain the super-hydrophilic micro-nano structure liquid absorbent core product.
6. The method for preparing an ultra-thin vapor chamber super-hydrophilic micro-nano structure liquid wick according to claim 5, characterized in that: The high surface energy treatment in step 4) is immersion, spraying, evaporation, and sputtering of SiO2 / TiO2 to form an oxide coating to achieve super-hydrophilic properties; and the thickness of the oxide coating is less than 5 nanometers.
7. The method for preparing an ultra-thin vapor chamber super-hydrophilic micro-nano structure liquid wick according to claim 5, characterized in that: The wavelength of the ultrafast laser can be near-infrared light, green light or ultraviolet light; the repetition frequency of the ultrafast laser is 10KHz-10000KHz, the average power is 1-500W, the scanning speed is 10-10000mm / s, the focal spot size is 1-300 microns, and the scanning times are single or multiple.
8. The method for preparing an ultra-thin vapor chamber super-hydrophilic micro-nano structure liquid wick according to claim 7, characterized in that: The ultrafast laser is a picosecond laser or a femtosecond laser. The pulse width of the picosecond laser is 1-1000 picoseconds, and the pulse of the femtosecond laser is 50-1000 femtoseconds.
